Assessment of sediment replenishment volume in Langat River system - Mahmud, Nur Hidayah Huqmah; Jamil, Nor Rohaizah; Abdullah, Ahmad Fikri; Sulaiman, Mohd Sofiyan (Faculty of Science, University of Malaya, 2022)
The river sand mining activity has taken place in a sand-bed river system in Selangor, Malaysia for decades even before the legalisation was initiated in 2008. This study focuses on the determination of optimum sand extraction for low-flow and high-flow seasons. The sand replenishment rate was used as the benchmark in determining the threshold level of the extractable rate in the Langat River, Selangor system. The total sediment load was computed using Yang (1973) equation due to the high percentage of agreement between the predicted sediment load and measured sediment load. Almost 41.6% of the predicted data fall within the allowable discrepancy ratio test between the predicted value and measured value. The comparison of sand replenishment rate in high and low flow seasons proved that the river system has quicker capabilities in sand replenishment rate at the extraction point during the high-flow season compared to the latter by 83%. The quantifiable volume of the extractable sand rate is proposed specifically during low-flow months (May to September) whereby the slower replenishment rate is critical and riskier. The optimal sand mining volume during the low-flow months is calculated by reducing 10% from the total replenishment volume and the recommended optimum extraction load has been delivered by the number of 25 tons lorries for easier observation by the contractor and authority’s body. The monthly optimum extraction in Langat River during low-flow months is calculated at a minimum of 437 trucks to a maximum of 20,114 trucks per month.